INTERNET SLANG AND DIGITAL NEOLOGISMS IN ITALIAN: IMPACT ON TRADITIONAL LINGUISTICS - Seliverstova, Anastasiia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article studies the use and role of Internet slang and digital neologisms in Italian language. It is stated that with the development of social media, chats, and digital platforms, daily language is undergoing rapid and significant transformations. Italian neological units and the use of specific Internet slang, often created to respond to the unique communicative needs of the online environment, raise questions about the future of the Italian language and its evolution. The reasons for the emergence of digital neological units and Internet slang have been mentioned. The examples of Internet lexical units have been selected and analyzed, the perspectives of the study have been described. The article delves deeper into the implications of these linguistic changes, exploring how Internet slang reflects cultural shifts and societal trends. The role of youth culture in shaping language is emphasized, as younger generations adapt their communication styles to fit the fast-paced digital landscape. Additionally, the study considers how these neologisms can both enrich and challenge the traditional norms of the Italian language. By examining specific case studies of commonly used terms and phrases, the article aims to provide insights into the dynamics of language evolution in the digital age and its potential impact on future linguistic practices. The active use of borrowed and altered anglicisms in Italian is observed. It was concluded that the phenomenon of Internet slang and digital neologisms is the one changing linguistic norms, influencing grammatical structures and challenging traditional approaches to language learning. As it is claimed, the studied topic represents a fertile field for research and offers opportunities to investigate how the Italian language is transforming in the digital age._______________References:• Baron, S. (2008). Always on: Language in an online and mobile world. Oxford University Press.• Crystal, (2006). Language and the internet (2-nd ed.). Cambridge University Press. Sources:• Corriere della Sera (2024). Così una fabbrica di bot russi ha cambiato il poker online: il segreto del successo è un'IA che sa bluffare. URL: https://www.corriere.it/tecnologia/ 24_settembre_27/cosi-una-fabbrica-di-bot-russi-ha-cambiato-il-poker-online-il-segreto-del-successo-e-un-ia-che-sa-bluffare-401fcf8b-1c63-4e92-acc1-4c415d3bexlk.shtmlю• Corriere della Sera (2024). Boomer? Risorse umane da valorizzare: le aziende hanno bisogno degli over 55, ecco come attrarli. URL: https://www.corriere.it/economia/lavoro/ 24_maggio_01/boomer-risorse-umane-da-valorizzare-le-aziende-hanno-bisogno-degli-over-55-ecco-come-attrarli-9a4cb243-eb50-4a38-ab0b-3461d26e7xlk.shtml;• La Repubblica (2023). Cringe: cosa significa? Una nuova voce del dizionario generazionale a cura dei giovani Holden. URL: https://www.repubblica.it/moda-e-beauty/d/2023/10/ 26/news/significato_parola_cringe_giovani_holden-414604403/.• Quali sono le boss fight più difficili ì. URL, https://www.everyeye.it/notizie/boss-fight-difficili-giochi-souls-fromsoftware-583166.html.• Corriere della Sera. Vacanze relax nelle fincas. URL: https://www.corriere.it/ viaggi/viaggi_tendenze/mete_scoprire/2005/06_Giugno/13/ibiza.shtml;• URL: https://www.linoolmostudio.it/blog/hai-gia-droppato-su-instagram-e-forse-neanche-lo-sai/• Corriere della Sera (2024). URL: https://www.corriere.it/opinioni/24_luglio_01/caro-vocabolario-lasciati-skippare-b104b067-624b-4376-a334-8f4ec875fxlk.shtml.• Il Sole 24 Ore (2022). Come funziona la Blockchain. URL: https://www.ilsole24ore.com/art/come-funziona-blockchain-AEk3yJOB.• Corriere della Sera (2024). Dalle criptovalute alla token economy. URL: https://studio.corriere.it/swaggy-sa01-token-economy/
Keywords: Internet slang, digital neologisms, social media, digitalization, online environment, anglicisms